Tunable capacitance multiplier with a single voltage differencing buffered amplifier - Unhavanich, Sumalee; Onjan, Oosana; Tangsrirat, Worapong (My University, 2016)
This work describes the grounded electronically tunable capacitance multiplier circuit using voltage differencing buffered amplifier (VDBA) as an active element. The proposed capacitance simulator is simulated using one VDBA, one floating capacitor and one grounded resistor. The realized equivalent capacitance can be tuned electronically through the (ransconductance gain of the VDBA. The effect of the VDBA non-idealitles on the realized equivalent capacitance has also been discussed in detail. As an application, active RC lowpass filter is realized using the proposed tunable capacitance simulator. PSPICE simulation results show a good agreement with the theoretical analysis, and veri1 the behaviors of the proposed simulator and its application.
Keywords: Capacitance multiplier; Impedance simulator; Voltage differencing buffered amplifier (VDBA)